Examining the role of glycoside hydrolases in local rheology of Pseudomonas aeruginosa biofilms - Bhattarai, Bikash; Christopher, Gordon F. (Frontiers in Physics, 2023)
Current research strategies in the treatment of biofilm have focused on dispersal, in which bacteria are made to vacate the extracellular polymeric substance (EPS) surrounding them and return to a planktonic state where antimicrobial treatments are more effective. Glycoside hydrolases (GH), which cleave bonds in EPS polysaccharides, have been shown to promote dispersal in Pseudomonas aeruginosa biofilms. The dispersal mechanism is possibly due to GHs’ ability to directly release bacteria from the EPS, disrupt EPS’ ability to regulate environment, or reduce overall mechanical stability. In this work, passive microrheology is used to examine the relevance of the last mechanism by exploring the effects of 3 GH’s (-amylase, cellulase, and xylanase) known to disperse P. Aeruginosa on local biofilm viscoelasticity. In comparison to control studies in wild type strains, it is found that treatment by all 3 GHs result in statistically less relatively elastic and stiff biofilms, indicating that changes to mechanical stability may be a factor in effective dispersal. Both cellulase and xylanase were observed to have the greatest impact in creating a less stiff and elastic biofilm; these GHs have been observed to be effective at dispersal in published results. Each GH was further tested on biofilms grown with strains that produced EPS missing specific polysaccharide components. Cellulase specifically targeted Psl, which forms the major structural and mechanical backbone of the EPS, explaining its efficacy in dispersal. However, xylanase did not appear to exhibit any affinity to any polysaccharide within the EPS based on the microrheology results. Overall, these results suggest that the local microrheology of the biofilms are impacted by GH’s and that may be one of the factors that is causing the ability of these therapeutics to enhance dispersal.